Pengaruh Kelengkapan Fasilitas Belajar Pendidikan Agama Islam Terhadap Hasil Belajar Siswa Di UPT. SD Negeri 16 Sido Mulyo Kecamatan Medang Deras Kabupaten Batu Bara - Nurmalena Julyanti; Sari Atika Parinduri; Indah Dina Pratiwi (STAI Tebing Tinggi Deli, 2023)
This research approach is a quantitative approach, namely research where the data obtained is related to numbers which causes the use of statistical analysis techniques. The results of the research in this thesis, based on calculations, the coefficient of determination is 18.31%. Thus it can be seen that the value of the contribution of the completeness of learning facilities in the subject of Islamic Religious Education to the learning outcomes of UPT students. SD Negeri 16 Sido Mulyo, Medang Deras District, Batu Bara Regency by 18.31% and the remaining 82% (100% -18%) is influenced by variables that were not examined in this study such as learning motivation, learning environment, methods and learning strategies and so on. The results of the analysis show that in the product moment value table